SOSIALISAI POLA HIDUP DAN POLA MAKAN YANG BAIK UNTUK MENCEGAH TERJADINYA GASTRITIS PADA SISWA SMK IBRAHIMY 1 DI P2S2 SUKOREJO - Gasim Soka, Burhanudin; Kholidah, Nur Diana (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM, 2024)
Gastritis is inflammation that affects the gastric mucosa. One way to prevent gastritis is to make it a habit to eat regularly, avoid foods that trigger gastritis and reduce stress. This community service aims to increase public knowledge, especially students of P2S2 Sukorejo, Situbondo Regency, to find out good lifestyles and eating habits as a prevention of gastritis. The method used is conducting health education and distributing leaflets on counseling materials. The results showed that 95.16% of respondents said they knew gastritis after delivering the material. 96.77% of respondents stated that the material presented was clear. 85.48% of respondents stated that the material presented was in accordance with the constraints experienced by students/santri. 93.55% stated that they had the opportunity to ask questions and express opinions. 98.39% of respondents stated that the activities provided benefits to the participants.